Assessing the impact of different industries on the economic trend of Dhaka region: A short-run and long-run approach - Hossain, Md Toufiq; Rana, Md Juwel; Das , Anutosh; Roy, Sumita (Journal of Bangladesh Institute of Planners, 2025)
The economic trend of a region plays a crucial role in the overall development and growth of a nation. This paper aims to assess the impact of different industries on the economic trend of the Dhaka region in Bangladesh. Specifically, it focuses on determining the contribution of regional GDP to the national GDP through various industries. To achieve the aim, this study employs a short-run and a long-run approach of regional economic structure analysis. The short-run analysis allows for an examination of the immediate impact of industries on the Dhaka region's economic trend. On the other hand, the long-run analysis considers the sustained effects of industries over an extended period. Data for this research paper were collected from government reports, statistical databases, and are industry specific data. The analysis encompassed a wide range of sectors such as manufacturing, services, agriculture, and construction, among others to do short run and long run analysis by calculating economic base multiplier, national share, industry mix shift share and regional shift share. The results of this study provide a comprehensive understanding of the industries that have a substantial contribution to the economic trend of the Dhaka region. Furthermore, it provides insights into the extent of the region's impact on the national GDP through these industries as it determines regionally and nationally fast or slow growing industries. The findings from this research demonstrate that Dhaka Region’s industries contributed 19% of the national GDP in 1999–2000, showcasing its economic importance which outpaced national average growth of industries but faced challenges in some sectors. This study sheds light on the short and long-term impacts of different industries on the economic trend of the Dhaka region in Bangladesh. JBIP, Vol. 17, 2024, pp. 11-33